Windows 7 SP1 quicksteps - Matthews, Martin S. (QuickSteps., 2011)
"This full-color, visual guide to Windows 7 is the fastest, easiest way to get up and running on the latest version of Windows.Windows 7 SP1 QuickSteps is filled with color screenshots and step-by-step instructions to help you get started on Windows 7 Service Pack 1. Learn how to customize the interface, manage files and programs, connect to the Internet, set up and use email, establish a network, control security, and enjoy movies and music. The book covers the essentials up to more advanced features of Windows 7. Windows 7 SP1 QuickSteps Covers all that's new in Windows 7 Service Pack 1 Includes details on Internet Explorer 9, Windows Live Mail 2011, and Windows Live Essentials Features full-color graphics along with step-by-step tutorials High production value, loads of information, and an low price make this book the best value on the market"--